1999
DOI: 10.1161/01.atv.19.4.990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lp(a) on the Early Functional and Structural Changes of Atherosclerosis

Abstract: Abstract-Epidemiologic studies have shown a significant relationship between elevated plasma levels of Lp(a) and increased risk of cardiovascular events; however, the mechanisms by which elevated Lp(a) levels produce this increased risk are not known. To test the hypothesis that high Lp(a) levels might contribute to the development of subclinical atherosclerosis, we examined the influence of Lp(a) levels on early functional and structural atherosclerotic vascular changes. Flow-mediated (endothelium-dependent) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
5
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 72 publications
2
26
5
1
Order By: Relevance
“…10,2004 Wu et al May 19, 2004May 19, :1828 Effect of Lp(a) and apo(a) on Endothelial Function the vasculature related to Lp(a). These observations seem to differ from those recently reported by Raitakari et al (19). Using similar methodology, these investigators found Lp(a) levels not to correlate with either FMD or with carotid intimal-medial disease.…”
contrasting
confidence: 88%
“…10,2004 Wu et al May 19, 2004May 19, :1828 Effect of Lp(a) and apo(a) on Endothelial Function the vasculature related to Lp(a). These observations seem to differ from those recently reported by Raitakari et al (19). Using similar methodology, these investigators found Lp(a) levels not to correlate with either FMD or with carotid intimal-medial disease.…”
contrasting
confidence: 88%
“…This has led to speculation about a possible atherogenic effect of rhGH treatment in pediatric renal failure [10]. Endothelial function, as measured by FMD, does not seem to be influenced by Lp(a) levels [25,26]. Therefore, our study does not rule out a possible detrimental effect of rhGH treatment on the vascular wall through an increase in Lp(a) levels.…”
Section: Discussionmentioning
confidence: 76%
“…31,32 The association between carotid and coronary atherosclerosis is only marginally increased when information of IMT from the internal carotid and carotid bulb are added to the common carotid IMT, supporting that the use of common carotid IMT may be preferable for certain analyses. 31 IMT measurements of the common carotid artery correlate significantly with traditional risk factors, 4,[33][34][35] with the occurrence of cerebrovascular disease, 6,36 and with the severity and extent of coronary heart disease. 10 Although IMT values cannot be used to predict the risk of coronary heart disease on an individual basis, 10 they can nevertheless predict the likelihood of cardiovascular events in population groups.…”
Section: Table 3 Linear Regression Coefficients On the Relation Of Imentioning
confidence: 96%